The construction technology handbook - Seaton, Hugh (Wiley, 2021)
Tired of new software that doesn't seem to work in the field? Ready to get your teams up to speed and productive with the latest tools?   The Construction Technology Handbook takes a ground up, no jargon look at technology in the construction industry. From clear, quickly grasped explanations of how popular software actually works to how companies both large and small can efficiently try out and onboard new tools, this book unlocks new ways for construction field teams, firm owners, managers, leaders, and employees to do business.  You'll learn about:  Simple frameworks for making sense of all the new options cropping up  How software and data work and how they work together to make your job easier and safer  What artificial intelligence really is and how it can help real companies today  Tools that are just over the horizon that will, one day, make your job just a little bit easier  New and practical resources to help you incorporate an attitude of innovation and technology adoption into your workplace  Perfect for general contractors and subcontractors, The Construction Technology Handbook also belongs on the bookshelves of construction technology vendors and construction workers who want to better understand the needs of the construction industry and the inner workings of construction technology, respectively.